Evaluation of the cytotoxic effects and apoptosis inducing of Cuscuta epithymum extract on esophageal squamous cell carcinoma - M. Hashemi; A. Panahi; R. Nosrati; G. D. Oranj; R. Jafari-Shakib (Сибирский онкологический журнал, 2024)
Background. Esophageal cancer is the eighth most common cancer in the world. The antitumor effects of medicinal plants have been shown as a therapeutic strategy to treat esophageal cancer. This study aimed to evaluate in vitro effects of Cuscuta epithymum extract on the survival and apoptosis of esophageal cancer cell line. Material and Methods. Here, the hydroalcoholic Soxhlet extract of C. epithymum plant was prepared. The cell viability of esophageal cancer cell line KYSE-30 was evaluated by MTT assay after 24 h treatment with concentrations of 50, 100, 200, 400, 600, 800 and 1000 μg/ml of the extract. Then, the apoptotic effect of extract was evaluated by flow cytometry using Propidium Iodide (PI) staining and sub-G1 peak analysis, and Annexin V-FITC/PI staining in cells treated with concentrations of 125, 250, 500 and 750 μg/ml as well as morphological change of healthy cells to apoptotic and necrotic form. Results. The hydroalcoholic extract of C. epithymum decreases the viability of KYSE-30 cells in a dose-dependent manner with an IC50 of 646 µg/ ml at 24 h. A significant increase was observed in the percentage of sub-G1 phase in cells treated with 500, 750, and 1000 μg/ml of C. epithymum extract for 24 h compared to the control group (p<0.01 and p<0.001). The results also showed a significantly enhanced the percentage of primary and secondary apoptotic cells compared to untreated cells. At concentrations of 250, 500, and 750 µg/ml, approximately 17, 33 and 45 % of cells was apoptotic. The apoptotic and necrotic cells morphology after treatment with 250 and 500 µg/ml of the extract was also confirmed by fluorescence microscopy. Conclusion. The findings showed the apoptotic effect of the hydroalcoholic extract of C. epithymum on KYSE-30 cells in vitro. The effect of this extract on the genes involved in apoptosis as well as the mechanism of action of this extract are recommended.